Utilizing Zebrafish to Identify Anti‐(Lymph)Angiogenic Compounds for Cancer Treatment: Promise and Future Challenges. (August 2016) - Okuda, Kazuhide S.; Lee, Hui Mei; Velaithan, Vithya; Ng, Mei Fong; Patel, Vyomesh
Abstract: Cancer metastasis which predominantly occurs through blood and lymphatic vessels, is the leading cause of death in cancer patients. Consequently, several anti‐angiogenic agents have been approved as therapeutic agents for human cancers such as metastatic renal cell carcinoma. Also, anti‐lymphangiogenic drugs such as monoclonal antibodies VGX‐100 and IMC‐3C5 have undergone phase I clinical trials for advanced and metastatic solid tumors. Although anti‐tumor‐associated angiogenesis has proven to be a promising therapeutic strategy for human cancers, this approach is fraught with toxicities and development of drug resistance. This emphasizes the need for alternative anti‐(lymph)angiogenic drugs. The use of zebrafish has become accepted as an established model for high‐throughput screening, vascular biology, and cancer research. Importantly, various zebrafish transgenic lines have now been generated that can readily discriminate different vascular compartments. This now enables detailed in vivo studies that are relevant to both human physiological and tumor (lymph)angiogenesis to be conducted in zebrafish. This review highlights recent advancements in the zebrafish anti‐vascular screening platform and showcases promising new anti‐(lymph)angiogenic compounds that have been derived from this model. In addition, this review discusses the promises and challenges of the zebrafish model in the context of anti‐(lymph)angiogenic compound discovery for cancer treatment.